Interferensi Linguistik dalam Karangan Bahasa Arab di Kalangan Siswa Kelas XI MA Al-Falah Jakarta Timur - Putri, Firwana Ayudhia; Qomaruzzaman, Qomaruzzaman; Susiawati, Wati (Kalimatuna: Journal of Arabic Research, 2023)
This research aims to describe the phenomenon of syntactical interference in directed construction, to reveal the causes of syntactical interference and the efforts made to reduce the occurrence of syntactical interference. The method of this research is qualitative descriptive method. The researcher uses these methods in collecting data: observations, interviews and directed construction for eleventh grade students. This research encovers that they are are four phenomena of syntactical interference in directed construction among eleventh grade students at Al-Falah Islamic Secondary School; in matching; in the noun of the number; in the noun of the adjective; and in the lack of vocabulary. The factors that cause syntactical interference are: lack of vocabulary and lack of Arabic grammar mastery. The efforts to reduce the incidence of interference are: changing teaching methods, teaching techniques in correcting students mistakes, and conducting an activity to assess learning materials.